Metallo‐supramolecular nanofibers based on type‐I photosensitizer for synergistic antibacterial therapy - Shibo Lyu; Lukun Li; Jingdong Gao; Dapeng Liu; Fengling Song (Smart Molecules)
Abstract Photodynamic therapy (PDT) has shown great merits in treating microbial infections due to its absence of bacterial resistance. However, the pronounced hypoxic microenvironment in the bacterial infections limits the therapeutic efficiency of traditional type‐II PDT, which is highly dependent on oxygen. Here type‐I photosensitizer BTZn‐Py (n = 8, 20) coordinates with chemical antibacterial agent Ag+ to fabricate metallo‐supramolecular nanofibers. Under light irradiation, the formed nanofibers could not only generate type‐II reactive oxygen species (ROS), 1O2, but also produce type‐I ROS O2•− which addressed the hypoxic issues within infected tissues. Moreover, the acid‐ and photo‐active Ag+ release from the nanofibers endowed the metallo‐supramolecular nanofibers with controlled release characteristic, which showed good biocompatibility to normal tissues. Owing to controlled Ag+ release and photoinduced type‐I ROS, the in vitro and in vivo experiments confirmed the significantly synergistic antibacterial performance of the metallo‐supramolecular fibers against both Gram‐positive and Gram‐negative bacteria.